2020
DOI: 10.1590/1980-5918.033.ao13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gross motor coordination between overweight/obese and eutrophic children

Abstract: Introduction: Overweight and obese children may have lower motor coordination score than normal-weight children. Objective: To compare gross motor coordination between overweight/obese and normal-weight children and investigate the associated factors with the motor coordination scores. Method: This cross-sectional study involved 169 children of both genders, aged 6-9 years. Children with malformations, bone, muscle, and joint or neurological disorders, and BMI z < -2 were excluded. Gross motor coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the last 10 years, among the studies published with the KTK, the works that aimed to analyze the association between performance in their tasks and the BMI of children and young people stood out, due to their pioneering spirit and greater number of publications, either in cross-sectional [11,24,25], longitudinal [26], as well as, in systematic review with meta-analysis [27]. The evidence showed that overweight and obese individuals had worse KTK performances compared to their normal weight peers.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 10 years, among the studies published with the KTK, the works that aimed to analyze the association between performance in their tasks and the BMI of children and young people stood out, due to their pioneering spirit and greater number of publications, either in cross-sectional [11,24,25], longitudinal [26], as well as, in systematic review with meta-analysis [27]. The evidence showed that overweight and obese individuals had worse KTK performances compared to their normal weight peers.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, no official estimate of poor motor coordination exists, possibly because of the country’s continental dimension, a low prevalence of PE classes in schools, and a low number of accessible (free) tools to promote the development and assessment of motor coordination in Brazilian children and adolescents, complicating measurements within the context of PE (Silva & Beltrame, 2013). However, in the last decade, studies, including those of Brazilians, have shown that students’ motor coordination is poor in relationship to age or level of motor development (Andrade et al, 2020; Luz et al, 2015; Moreira et al, 2014; Nobre et al, 2014; Santos et al, 2013, 2015, 2016; Santos & Ferracioli, 2020; Santos & Vieira, 2013; Silva & Beltrame, 2013; Valentini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no gold standard instrument to assess motor coordination performance, several validated tests have been proposed for different populations and in different fields of sports science: Test of Gross Motor Development 2 – TGMD-3 (Ulrich, 2016); Motor Scale Development - MSD (Rosa Neto et al, 2010); the Bruininks-Osertsky Test of Motor Proficiency Second Edition - BOT-2 (Andrade et al, 2020; Bruininks & Bruininks, 2005); the Körperkoordinationstest für Kinder - KTK (Kiphard & Schilling, 1974; Moreira et al, 2019); the Movement Assessment Battery for Children MABC-2 (Henderson et al, 2007; Valentini et al, 2014); the Assessment of Basic Motor Competencies - Motorische Basiskompetenzen - MOBAK (Herrmann et al, 2015); the Wiener Koordinationsparcours - WKP (Warwitz, 1982); and the Evaluation of the Motor Coordination with Ball - TECOBOL (Silva, 2010), among others. The use of these tools is beneficial, because they provide standardized assessment procedures, comparative norms, and valid and reliable information for diagnosing possible motor deficits and designing intervention programs in different areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation